THE ANALYSIS OF STUDENTS ENGLISH ABILITY THROUGH SELECTED RESPONSE TYPE BY SOCRATIVE APP - Herawati, Herawati; Agustin, Ariya (STKIP PGRI Bandar Lampung, 2021)
This paper aims to analyze the students’ English ability through selected response type by Socrative APP. The instruments of the test were multiple choice items and semi-structure interview to the students and lecturers. The tests were used multiple-choice items that consisted of 45 items; 25 items for structure and for reading sections 20 items. The test was designed based on the validity, reliability and curriculum. The sample of this research was 32 students of the first semester in Musi Rawas University. The result of this study showed that the students were mastered structure/grammar section more rather than reading section test. Their lecturers often taught grammar rather than reading and their lack of interest in reading were the reasons.